Smart Nanocarriers in Targeted Drug Delivery: Advances, Challenges, and Future Directions - Navitha, G. A.; Likitha, K. (Journal of Pharmacy Practice and Community Medicine)
Nanocarrier-assisted Smart Drug Delivery Systems (SDDS) are one of the most revolutionary advances in contemporary medicine. Nanodelivery systems have been developed for improved therapeutic accuracy, higher bioavailability, and lower systemic toxicity. Different from conventional formulations, the smart nanocarriers respond to stimuli and incorporate surface engineering, molecular targeting and controlled drug release toward improved PK-PD performance. In the past 10 years, progress in material science, lipid technology, polymer chemistry and knowledge about nanobio interface have allowed the formulation of novel nanocarrier systems. These systems consist of liposomes, polymeric NPs, dendrimers, nanogels, Solid Lipid Nanoparticles (SLNs) and Nanostructured Lipid Carriers (NLCs), metallic nanoparticles, and biomimetic nanosystems as well as hybrid multifunctional constructs. These carriers can respond to both internal (pH, redox, enzymes, hypoxia and reactive oxygen species) and external (light, heat, magnetic fields, ultrasound, and electric fields) stimuli in a smart way, leading to controlled release and better therapeutic efficacy. Smart nanocarriers have shown excellent capacity for delivering cancer-targeted therapy, neurotherapy, infectious disease management, metabolic disorder management, cardiovascular diseases treatment, immunotherapy, gene therapy, and vaccination. Recent progress can be noted in the cell membrane-coated nanoparticles, lipid nanoparticle for mRNA vaccine, CRISPR/Cas9 carrier and AI-assisted design of nanocarriers, nanotheranostics and nanorobotic targeting. Despite their promising aspects, challenges remain in nanotoxicology, mass production, regulatory uniformity and evidence of long-term safety. This review provides an in-depth discussion on SDDS, including their mechanisms of action, stimulus-response mode, therapeutic applications and technological progress, for the period from 2020 to 2024, as well as safety considerations, regulatory aspects, challenges in the translation, and future directions. A structured approach incorporating PubMed, Scopus, ScienceDirect, and other electronic databases was adopted to extract the latest literature. In general, smart nanocarriers are appearing as the design elements that could revolutionize personalized medicine and targeted treatments.
Keywords: Controlled Release; Lipid Nanoparticles; Nanocarriers; Nanomedicine; Smart Drug Delivery; Stimuli-Responsive Systems; Targeted Therapy